Pemberdayaan Karang Taruna Desa Sidogede Melalui Pelatihan Digital Marketing untuk Pemasaran Hasil Bumi - Muhimatun, Atik; Muhyidin; Zulfa Nabila; Dwi Heriyanto; Sukris Sutiyatno; Titi Suwarni (Jurnal Inovasi Pengabdian Masyarakat, 2026)
This program aims to empower the Sidogede Village Youth Organization through digital marketing training to optimize the marketing of local produce. Digital transformation is seen as a strategic solution to overcome the problem of long distribution chains and low selling value that have relied on conventional systems. The implementation method uses a participatory-applicative approach in three core stages: preparation (observation, needs survey, module preparation), implementation of one-day intensive workshops based on learning by doing, and multi-level evaluation (reaction, learning, behavior, and online monitoring). The results of the training showed a significant transformation in capacity: 100% of participants (20 people) successfully created and optimized Instagram/WhatsApp Business business accounts and produced marketing content. Seven-day post-training monitoring revealed that 75% of participants actively posted with an engagement rate of 3.5%, as well as 5 initial transactions worth IDR 850,000. This program proves that systematic mentoring can bridge the digital divide, change the mindset from consumers to content producers, and create real economic impacts. The sustainability of the program is supported by the formation of the Karang Taruna social media management team structure and the collective commitment to consistently provide content.